Cardiomyocyte‐specific miR‐100 overexpression preserves heart function under pressure overload in mice and diminishes fatty acid uptake as well as ROS production by direct suppression of Nox4 and CD36. Issue 11 (4th October 2021) - Smolka, Christian; Schlösser, Delia; Koentges, Christoph; Tarkhnishvili, Aleksandre; Gorka, Oliver; Pfeifer, Dietmar; Bemtgen, Xavier; Asmussen, Alexander; Groß, Olaf; Diehl, Philipp; Moser, Martin; Bode, Christoph; et al.
Abstract: MicroRNAs are key regulators of the cardiac response to injury. MiR‐100 has recently been suggested to be involved in different forms of heart failure, but functional studies are lacking. In the present study, we examined the impact of transgenic miR‐100 overexpression on cardiac structure and function during physiological aging and pathological pressure‐overload‐induced heart failure in mice after transverse aortic constriction surgery. MiR‐100 was moderately upregulated after induction of pressure overload in mice. While in our transgenic model the cardiomyocyte‐specific overexpression of miR‐100 did not result in an obvious cardiac phenotype in unchallenged mice, the transgenic mouse strain exhibited less left ventricular dilatation and a higher ejection fraction than wildtype animals, demonstrating an attenuation of maladaptive cardiac remodeling by miR‐100. Cardiac transcriptome analysis identified a repression of several regulatory genes related to cardiac metabolism, lipid peroxidation, and production of reactive oxygen species (ROS) by miR‐100 overexpression, possibly mediating the observed functional effects. While the modulation of ROS‐production seemed to be indirectly affected by miR‐100 via Alox5‐and Nox4‐downregulation, we demonstrated that miR‐100 induced a direct repression of the scavenger protein CD36 in murine hearts resulting in a decreased uptake of long‐chain fatty acids and an alteration of mitochondrial respiratory function with an enhanced glycolytic state. In summary, we identified miR‐100 as a modulator of cardiac metabolism and ROS production without an apparent cardiac phenotype at baseline but a protective effect under conditions of pressure‐overload‐induced cardiac stress, providing new insight into the mechanisms of heart failure.